2015
DOI: 10.1212/wnl.0000000000001870
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of familial amyloidotic polyneuropathy

Abstract: Objectives: To assess the association between severity of neuropathy and disease stage, and estimate the rate of neuropathy progression in a retrospective cross-sectional analysis of a multinational population of patients with familial amyloidotic polyneuropathy (FAP). Methods:We characterize neuropathy severity and rate of progression in available patients with FAP in France, the United States, Portugal, and Italy. Neuropathy Impairment Scores (NIS), time from symptom onset to NIS measurement, polyneuropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 30 publications
7
124
0
4
Order By: Relevance
“…Presenting symptoms and disease course of ATTR-FAP are influenced by the underlying TTR mutation and by geographic location [3][4][5]. The most common and widely studied TTR mutation worldwide is ATTRV30M (p.TTRV50M) [1,6]; non-ATTRV30M mutations are increasingly reported and often associated with a higher incidence of mixed phenotypes (neuropathy, cardiomyopathy and leptomeningeal complications) and with a more rapid and severe disease course [5].…”
Section: Introductionmentioning
confidence: 99%
“…Presenting symptoms and disease course of ATTR-FAP are influenced by the underlying TTR mutation and by geographic location [3][4][5]. The most common and widely studied TTR mutation worldwide is ATTRV30M (p.TTRV50M) [1,6]; non-ATTRV30M mutations are increasingly reported and often associated with a higher incidence of mixed phenotypes (neuropathy, cardiomyopathy and leptomeningeal complications) and with a more rapid and severe disease course [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 TTR is a 55kD protein that transports thyroxine and retinol-binding protein in the blood and cerebrospinal fluid (CSF) and normally exists as a tetramer. 5 Classical symptoms of TTR-FAP occur symmetrically in the distal lower extremities with tingling and prickly burning sensations of pain, suggesting early injury of small nerve fibers. [2][3][4] TTR-FAP is a progressive, disabling neuropathy affecting the autonomic, sensory, and motor components of the peripheral nerve system.…”
mentioning
confidence: 99%
“…In a recently published multinational study, rapid progression of FAP was demonstrated using the Neuropathy Impairment Score (NIS), and its severity was correlated with functional scales of locomotion …”
mentioning
confidence: 99%